Rights of Human and Nonhuman Animals: Complementing the Universal Declaration of Human Rights - Anne Peters (AJIL Unbound, 2018)
In May 2018, U.S. President Donald Trump spoke about illegal border crossings: “We have people coming into the country, or trying to come in … . You wouldn't believe how bad these people are. These aren't people. These are animals.” Such dehumanization (in this case of undocumented migrants at the U.S.-Mexico border) has been a standard discursive strategy to prepare, instigate, facilitate, and exculpate violence committed by humans against other humans throughout history. It is exactly in reaction to excesses of such dehumanizing mass violence committed in the Third Reich and during World War II that the Universal Declaration of Human Rights (UDHR) was adopted in 1948. This essay argues that the objectives of the UDHR itself would be furthered if the United Nations (or another international body such as the Food and Agriculture Organization, the World Health Organization, or the World Organisation for Animal Health (OIE)) engaged in work on a universal animal rights declaration. While animal welfare is increasingly protected in domestic jurisdictions, animal rights are still hardly recognized, although they would serve animals better. Animal rights would need to be universalized in order to have an effect in a globalized setting. The international legal order is flexible and receptive to nonhuman personhood. The historical experience with international human rights encourages the international animal rights project, because it shows how the equally pertinent objection of cultural imperialism can be overcome. Animal rights would complement human rights not least because the entrenchment of the species-hierarchy, as manifest in the denial of animal rights in many cases, condones disrespect for the rights of humans themselves.